Total Knee Arthroplasty Wrong Side Implant - Alanazi, Hassan; Alahmari, Mousa; Hashem, Musaab Abdullah; Alqahtani, Muath; Alanazi, Abdulaziz; Alenazi, Bashir (The Surgery Journal, 2018)
We report a unique wrong implant error during bilateral total knee replacement procedure in 72-year-old woman with bilateral knee osteoarthritis that failed conservative treatment. Patient has severe bilateral knee pain. Examination showed full range of motion. X-ray showed severe bilateral tricompartmental osteoarthritis. Patient underwent surgery in 2013; postoperative radiographs showed well-fixed femoral, tibial, and patellar components but right femoral implant was placed in the left knee. Postoperative examination showed painless full range of motion. One similar case report found describing wrong-site femoral component that ended with symptomatic. In our case, no complications were observed.
Keywords: arthroplasty; implant; osteoarthritis; wrong-site; knee; replacement